Nilai-Nilai Kepemimpinan Teungku Dayah dalam Pengelolaan Pendidikan Islam: Analisis Komparatif dengan Kepemimpinan Barat - M. Yunus; Muhammad Anggung Manumanoso Prasetyo; Nurlaila Nurlaila (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Teungku Dayah leadership holds a central position in Islamic education management in Aceh because it functions not only as an administrative mechanism but also as a source of moral, spiritual, and social legitimacy within dayah communities. Nevertheless, educational leadership studies remain largely dominated by Western paradigms emphasizing managerial rationality, while the values, meanings, and authority underlying Teungku Dayah leadership remain insufficiently examined, particularly in Aceh’s post-conflict and educational modernization contexts. This study aims to analyze the construction and representation of Teungku Dayah leadership values in Islamic education literature and conceptually compare them with Western leadership. It employs an interpretive qualitative approach using document analysis of relevant journal articles, conference proceedings, and academic works selected purposively. Data were analyzed through reflexive thematic analysis enriched by discursive reading. The findings identify three patterns: leadership as moral-spiritual authority, leadership as a rational managerial function, and leadership as negotiation between tradition and modernity. These findings reveal an epistemological tension between spiritual values and managerial rationality in Islamic educational leadership discourse. The study strengthens value-based and spiritual leadership perspectives and provides a conceptual foundation for developing a contextual Islamic educational leadership model rooted in Aceh’s sociocultural realities